Role of cyclic adenosine monophosphate (cAMP), cyclic guanosine monophosphate (cGMP) and p38 mitogen activated protein kinase (p38 MAPK) in preconditioning of the ischaemic myocardium - Marais, Erna (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2002.